EFFECTS OF DIFFERENT TYPES OF FEED ON GROWTH, SURVIVAL AND DIGESTIVE ENZYME ACTIVITY OF EARLY JUVENILE-STAGE MARBLE GOBY, Oxyeleotris marmoratus - Muhammad Darwis; Sitti Raehana Muhd. Shaleh; Masaru Tanaka; Shigeharu Senoo (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2008)
The stable mass seed production technique of marble goby, Oxyeleotris marmoratus has not yet been established due to high mortality occurring on the early juvenile stage and/or after 40 days after hatching (d AH). In order to establish the mass seed production technique, O. marmoratus juveniles of 40 d AH were reared for 60 days to determine growth, survival and digestive enzyme activity at different types of feed (trash fish, artificial feed and Artemia sp. nauplii). Specific growth rate (5.32) and survival rate (91.3%) in juveniles fed Artemia sp. nauplii showed significantly higher (P<0.05) than those of juveniles fed trash fish and artificial feed. At the end of the experiment, the mean specific trypsin, amylase and lipase activities of juveniles fed Artemia sp. nauplii were recorded as 0.04 mU mg protein-1m-1, 0.114 mg maltose mg protein-1h-1 and 9.58 m Units, respectively, and they were significantly higher than those of juveniles fed trash fish and artificial feed. In the present study it was shown that O. marmoratus early juveniles had more efficient digestibility and absorption the nutrient when fed with Artemia.